Forecasting Photovoltaic Module Remaining Life-Time Using Accelerated Aging Testing and Modelling on Aged Modules - Julien Dupuis; Christine Abdel Nour (SiliconPV Conference Proceedings)
This work investigates the possibility of predicting the remaining lifetime of a power plant by making accelerated aging testing on monocrystalline silicon cells modules working on a photovoltaic plant for eleven years in France and compares the results with the same testing done on modules from the same batch eleven years ago when they were new. The paper focuses on damp heat results. It is found that the degradation behaviour of the modules exposed outdoor has a similar trend compared to the modules tested eleven years ago when they were new but with a two-to-three-times quicker degradation. Moreover, electroluminescence characterization highlights some degradation differences, especially at the edges of the solar cells. Modelling the lifetime through empirical damp heat model on the used modules predict that degradation may accelerate after 3 to 4 years contrary to what was concluded based on the initial modules testing results eleven years ago: no degradation linked to heat and humidity conditions should have happened before 30 years.